2021
DOI: 10.3390/membranes11010060
|View full text |Cite
|
Sign up to set email alerts
|

Application of Silver-Loaded Composite Track-Etched Membranes for Photocatalytic Decomposition of Methylene Blue under Visible Light

Abstract: In this study, the use of composite track-etched membranes (TeMs) based on polyethylene terephthalate (PET) and electrolessly deposited silver microtubes (MTs) for the decomposition of toxic phenothiazine cationic dye, methylene blue (MB), under visible light was investigated. The structure and composition of the composite membranes were elucidated by scanning electron microscopy, energy dispersive spectroscopy, and X-ray diffraction technique. Under visible light irradiation, composite membrane with embedded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 69 publications
1
12
0
1
Order By: Relevance
“…In our previous studies, composite TeMs based on metals of the copper subgroup demonstrated high catalytic activity in various reactions types in both batch and flow-through modes [ 34 , 35 , 36 , 37 ]. For example, Ag/PET composites have proven to be effective photocatalysts for the removal of methylene blue dye [ 38 ], while CuO-based MTs have been shown to exhibit high efficiency in the sorption of As(III) ions [ 34 , 39 ]. Some important advantages of such catalysts and sorbents are their ease of use, low cost and ease of production, as well as the possibility for multiple reuses without additional activation and regeneration procedures, as shown in previous studies [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, composite TeMs based on metals of the copper subgroup demonstrated high catalytic activity in various reactions types in both batch and flow-through modes [ 34 , 35 , 36 , 37 ]. For example, Ag/PET composites have proven to be effective photocatalysts for the removal of methylene blue dye [ 38 ], while CuO-based MTs have been shown to exhibit high efficiency in the sorption of As(III) ions [ 34 , 39 ]. Some important advantages of such catalysts and sorbents are their ease of use, low cost and ease of production, as well as the possibility for multiple reuses without additional activation and regeneration procedures, as shown in previous studies [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, TeMs are used as filtration membranes for water purification [20,21] or effective adsorbents and are commercially available. Combining the inherent advantages of TeMs and metal nanostructures provides composite membranes that are excellent candidates in a variety of promising material science applications, such as biotechnology [22,23], catalysis [24][25][26][27][28], medicine [29,30], sensors [21,31], and radiation resistive and magnetic materials [32,33]. In our previous study, we created Cu/CuO in the nanochannels and surface of poly(ethylene terephthalate) (PET) TeMs by electroless template-assisted deposition of copper and subsequent low-temperature annealing process.…”
Section: Introductionmentioning
confidence: 99%
“…TeMs have a unique pore structure that offers the smallest tolerances regarding pore diameter and density compared with alternative porous membranes in the literature. The two-step process applied in their preparation (bombardment with accelerated heavy ions and subsequent chemical etching) allows them to precisely target specific requirements regarding the size and density of the nanochannels, which affect surface area, a key focus of absorption studies [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%